Archaeometallurgical characterization of Mediterranean discoidal shaped copper alloy ingots retrieved from sea environment. (February 2023) - Ashkenazi, D.; Beltrame, C.; Colpo, S.; Inberg, A.; Canovaro, C.; Artioli, G.
Highlights: The NAMA and NAMS ingots, retrieved from a sea environment, were studied by metallurgical analysis. All ingots were as-cast products made of copper with lead content. The NAMA and NAMS ingots were most likely manufactured in different workshops. The composition of the NAMA and NAMS ingots was different indicating dissimilar ore sources. Lead isotope analysis results of NAMS ingots are compatible with Iberian deposits. Abstract: Five copper ingots from the National Archaeological Museum of Aquileia (NAMA nos. 2, 3, 4, 7, 8) and four copper ingots from the National Archaeological Museum of the Sea (NAMS nos. 1, 2, 3, 4), retrieved from a sea environment, were the subject of the current study. The aim of this research is to apply a metallurgical approach in order to add further information about these objects, including their composition, microstructure, manufacturing process, and if possible, their origin. Samples were examined by a variety of testing methods, including visual testing, XRF analysis, metallographic examination, digital 3D multi-focal light microscope observation, SEM-EDS analysis, and lead isotope measurements (LIA). Cast defects were observed on both sides of the NAMA and NAMS ingots. Metallographic examination of the ingots from both collections revealed a dendritic microstructure typical to as-cast products. All ingots have a slight step on one side, probably resulting from plastic deformation, perhaps developed as a result of lifting them with a wrecking bar tool. Both the NAMA and NAMS ingots were made of copper with a small percentage of lead, yet their general composition was different. The better preservation of the NAMS ingots may probably result from the 0.1–0.5 wt% zinc content according to the XRF results. The inclusions observed in the NAMA ingots included Cu, Pb, O, Cl, As, Sb and Sn, while the inclusions observed in the NAMS ingots included Cu, Pb, O, Cl, Fe and a high content of sulphur (up to 21.9 wt% S). Based on their dissimilar bulk composition, the NAMA and NAMS ingots were most likely manufactured in different workshops and from dissimilar ore sources. The lead isotope ratios measured on the NAMS no. 1 sample are compatible with Iberian deposits of the Ossa Morena zone, and they are consistent with the published data available on coeval wrecked ingots from the Western Mediterranean.